Efficiency Evaluation of Silver Nanoparticles in the Controlling of the Fungi Associated with the Date Palm Offshoots - Alaa O. Manea; Mohammed A. Fayyadh; Yehya A. Salih (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Recently, Iraq has imported large numbers of tissue culture date palm offshoots from different countries. It is to build new orchards of date palm trees or plant them with the old orchards and some of them in the home's gardens. As a result of the widespread of many symptoms associated with these offshoots, this study was conducted in Basra Governorate, Iraq. To examine the capability of silver nanoparticles in controlling pathogens. The 36 fungi species were isolated from the shoot system of tissue culture date palm offshoots. Alternaria sp. was recorded at a high frequency compared to the Cladosporium spp. and Ulocladium spp. Neodieghtonia phoenicum, Scytalidium lignicola, and Neoscytalidium dimidiatum caused black scorch. Moreover, Phoma costarricensis has been recorded as causing the leaf spot disease. The roots infected by wilt disease have shown three various fungi, Fusarium solani, Fusarium proliferatum, and Fusarium fujikuroi. The study also illustrated that silver nanoparticles possessed a high ability to inhibit fungi growth in the laboratory.